Understanding mechanisms of change in psychotherapies for personality disorders - Kramer, Ueli; McMain, Shelley; Levy, Kenneth N. (Kenneth Neil) 1963- (Washington, DC American Psychological Association, 2024)
This book presents a holistic approach to treating patients with personality disorders that seeks to inspire psychotherapists and encourage innovation. Focusing on core mechanisms of change that span different therapeutic approaches, this book invites clinicians and researchers to join a dialogue with the authors, as they examine personality disorders from different theoretical perspectives, including dialectical behavior therapy, transference-focused therapy, plan analysis, clarification-oriented, and emotion-focused therapies. The authors explore five functional domains that underlie assessment and treatment for personality disorders: emotion dysregulation, disturbed social interaction, identity problems, impulsivity, and cognitive disturbances. Each domain is analyzed through an in-depth case example, with case conceptualizations and the careful evaluation of clinical decisions that must be made at key points in therapy. The authors then compare their different approaches, emphasizing commonalities among them while also pointing out notable differences. They also offer clear and compelling recommendations for maintaining and strengthening the therapeutic alliance. The final chapter synthesizes key takeaways from across the book to create a clear path towards enhancing clinical practice"-- Provided by publisher.
1. The importance of developing a focus on mechanisms of change in psychotherapy -- 2. Personality disorders: a conceptualization in functional domains -- 3. The first session of psychotherapy and getting started in treatment -- 4. Moving from emotional dysregulation to emotional balance -- 5. Moving from problematic social interactions to interpersonal effectiveness -- 6. Moving from identity diffusion to an integrated sense of self -- 7. Moving from impulsive behavior to self-reflection -- 8. Moving from cognitive-perceptual disturbances to coherent and reality-based narratives -- 9. Challenges in the therapeutic relationship and how to use them productively in psychotherapy -- 10. Discussing mechanisms of change in psychotherapies for personality disorders.
Includes bibliographical references and index.
Keywords: Personality disorders; Personality disorders -- Treatment; Psychotherapy -- Methodology